3-Phenyl-2-(piperidin-1-yl)-3,5,6,8-tetrahydro-4H-thiopyrano[3′,4′:2,3]thieno[5,4-d]pyrimidin-4-one - Xie, Hai (International Union of Crystallography, 2008)
In the title compound, C(20)H(21)N(3)OS(2), the piperidinyl ring has a distorted chair conformation. Weak intermolecular C—H⋯O hydrogen bonds link the molecules into centrosymmetric dimers. The crystal packing exhibits short intermolecular S⋯S distances of 3.590 (2) Å.